A System for Improving the Competence of Future Primary Class Teachers by Developing Divergent Thinking - Adizova Nigora Bakhtiyorovna (Researchparks Publishing, 2023)
In this article, I present opinions about the system of improving the teacher's qualifications through the development of divergent thinking in the conditions of modern education, the young generation's deep acquisition of knowledge and skills necessary for the development of society.